Investigating Factors Influencing Decision Makers to Adopt Accreditation Information System Using Multi Theory of Technology Acceptance Model, Resource Dependence Theory, and Technology-Organization-Environment: Evidence from Indonesian Private Universities - Hartono, Arif; Roostika, Ratna; Muslichah, Istyakara (International Review of Management and Marketing, 2025)
This study explores the factors influencing decision-makers adoption of the accreditation information system (AIS) in private universities across Yogyakarta, Surakarta, Magelang, Semarang, and Purwokerto, focusing on economics and business faculties accredited by LAMEMBA. Using a quantitative research design, data were collected from 300 decision-makers, including heads of study programs and program secretaries, through structured questionnaires. The analysis combined descriptive statistics with structural equation modeling (SEM) using SMART-PLS software to examine the relationships between latent variables. Findings reveal that financial costs and system complexity negatively influence AIS adoption, while perceived usefulness significantly drives adoption intentions. By integrating the technology acceptance model (TAM), resource dependence theory (RDT), and technology-organization-environment (TOE) framework, the study provides a holistic understanding of technology adoption in higher education. This comprehensive approach highlights the interplay of individual perceptions, external pressures, and organizational readiness in influencing adoption decisions. The study offers actionable insights for policymakers and academic leaders, contributing to the broader discourse on technology adoption in accreditation systems, particularly within developing countries like Indonesia. It underscores the importance of addressing financial and resource constraints to enhance the adoption of innovative systems in higher education.